SDG#4, 8 and 9 - Trends of Halal Audit Training with Blockchain Technology for Sustainable Development with Decent Job Creation - YEUNG, Shirley Mo Ching (Journal of Ecohumanism, 2025)
This paper outlines a comprehensive strategy to harness the power of integrated skills in technology, artificial intelligence (AI), blockchain, and halal concepts to rethink the design, delivery and assessment of the impact of halal training related courses under the green econmy. Aligning with the HKSAR policy address 2025, specifically paragraph 107, which emphasizes the enhancement of the General Employment Policy and the introduction of new mechanisms to attract top-tier talent, this project aims to position Hong Kong as a global/ virtual/ physical hub for halal training certificates in blockchain technology for revitalization. It seeks to address the acute manpower shortages - halal audit and halal executive competency in technology related training programmes in Hong Kong to promote SDG#9 innovations in the halal economy.